The Influence of Company Size and Leverage on Profitability Moderated by Environmental Performance - Ibnu Asif; Hadi Pramono; Hardiyanto Wibowo; Novi Dirgantari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Climate change caused by mining company operational activities can have a negative impact on the surrounding community. The purpose of this study is to determine the effect of company size and leverage on profitability, with environmental performance as a moderating variable. This research method uses a quantitative method with a sample of mining companies listed on the IDX during 2020–2023. This study found a positive relationship between company size and profitability, but leverage had a negative impact on profitability. Environmental performance as a moderator was unable to moderate the relationship between company size and profitability, but environmental performance could weaken the relationship between leverage and profitability.